Causality between PRONAF and family farmers' income between 2004 and 2015 (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
The National Program for Strengthening Family Farming (Programa Nacional de Fortalecimento da Agricultura Familiar – PRONAF, in Portuguese) led to several papers in the literature, many of them aiming to understand the impacts caused by PRONAF on economic growth. However, some studies attempt to explore the cause-effect relationship between rural credit granted by the program and income variables. This paper aims to understand, under the viewpoint of the causal relationship between PRONAF and the income of potential family farmers, to identify the effects of the Program, by verifying whether credit has a positive effect on the growth variables between 2004 and 2015 for Brazilian States. Results indicate Granger causality direction from credit to income, and the coefficients estimated in the panel show a positive effect of PRONAF on the income of potential family farmers selected from the National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios – PNAD, in Portuguese).